Institutional Ownership and Leverage on Earnings Management with Audit Committee as Moderation - Fidela Sahda Izdihar Widiana; Erni Harlina Isdiati (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
Economic choices heavily depend on financial reports. Yet, divergent motivations can drive managers to exploit accounting flexibilities to alter reported income. This investigation assesses how institutional shareholdings and financial leverage influence earnings management, considering the potential oversight role of the audit committee. The analysis utilizes 168 purposive observations from Indonesian food and beverage manufacturers between 2022 and 2024. Earnings interventions are quantified across discretionary accruals utilizing the Modified Jones Model, with evaluations conducted via Spearman correlation and multiple regression frameworks. The empirical outcomes reveal that neither institutional ownership nor leverage carry a meaningful statistical influence on financial reporting manipulations. Additionally, audit committees fail to alter these dynamics. These results imply that structural corporate governance frameworks remain insufficient to restrain accounting interventions under recent post-pandemic operational realities and heightened global credit strains